PENGARUH GENDER DAN SIKAP LOVE OF MONEY TERHADAP PERSEPSI ETIKA PENGGELAPAN PAJAK MAHASISWA AKUNTANSI (Studi Empiris Pada Mahasiswa Akuntansi FEB UNISMA) - Yayang Perdania Putri; M. Cholid Mawardi; Hariri Hariri (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study was conducted to determine the effect of gender and the attitude of love of money on the ethical perception of accounting students' tax evasion. This type of research uses quantitative research. The data collection used is primary data using a questionnaire or google form method. The research sample obtained was 81 students from the 2018 accounting department, FEB Islamic University of Malang, which were taken using the slovin formula. The analysis technique used is multiple linear regression analysis method using the SPSS 22.0. The results showed that simultaneously the two variables had a significant effect on the ethical perception of accounting students' tax evasion, while partially gender had an effect on the ethical perceptions of accounting students' tax evasion and love of money had no significant effect on the accounting students' ethical perceptions of tax evasion.Keywords: Gender, Love Of Money and Student Tax Evasion Ethics